Intracellular targeted delivery of quantum dots with extraordinary performance enabled by a novel nanomaterial design. Issue 2 (13th December 2018) - Wang, Jun; Dai, Jie; Yang, Xuan; Yu, Xiaoya; Emory, Steven R.; Yong, Xueqing; Xu, Jinhua; Mei, Ling; Xie, Jinbing; Han, Ning; Zhang, Xuejin; Ruan, Gang
Abstract : A new class of quantum dot probes based on hydrophobic nanoparticles is developed to achieve extraordinary intracellular targeted delivery performance. Abstract : Quantum dots (QDs) have emerged as a major class of fluorescent probes with unique optical properties, but applying QDs for imaging specific intracellular entities in live cells has been hindered by the poor performance of targeted intracellular delivery of QDs due to various cellular transport barriers. We describe a novel QD nanoprobe design, which is termed a cosolvent-bare hydrophobic QD-biomolecule (cS-bQD-BM, or 'SDot' for short), combining a cosolvent, a bare hydrophobic nanoparticle surface, ultrasmall size and biomolecular function. SDots show extraordinary intracellular targeting performance with the nucleus as the model target, including near-perfect specificity, excellent efficiency and reproducibility, high-throughput ability, minimal toxicity, and ease of operation, as well as superb optical properties and colloidal stability. We introduce integrated single-particle tracking and pair-correlation function analysis of a spinning-disk confocal microscope platform (iSPT-pCF-SDCM) to study SDot's cellular transport. Endocytosed SDots can undergo a highly potent and noninvasive process of vesicle escape, yielding complete vesicle escape with no serious vesicle disruption. We exploit SDots' unprecedented ability to overcome cellular transport barriers to enhance drug and macromolecule delivery.